DESIGN EVALUATION OF BROILER HOUSE IN REJO BINANGUN, KECAMATAN RAMAN UTARA, KABUPATEN LAMPUNG TIMUR - Nadzir, Nadzir (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The study aims to identify problems in broiler housnd evaluate design to increase productivity of broiler. The study was done from May – Juni 2015 at broiler house at Rejo Binangun, Kecamatan Raman Utara, East Lampung. Parameter observed and measured is: (1) the condition house in the study locations, including material house and size dimensions house; ( 2 ) environment parameter, includring to scatter temperature and RH, and distribution wind speed around the house; ( 3 ) comfort house parameter, including position broiler and mortality broiler; ( 4 ) ergonomic parameter; ( 5 ) evaluation design house. The result shown that design of broiler house was currently good, but need to repair on the floor and the stair. Broiler house performance was good, seen from broiler growth that reached standard weight, and mortality rates at 4 % or 60 broiler. Keywords: Design Broiler House, Design Evaluations, Broiler